The case of the haunted history museum - Brezenoff, Steven; Weber, Lisa K. (North Mankato, MN : Stone Arch Books, a Capstone imprint, 2015)
When a series of accidents and other strange happenings at the Capitol City Natural History Museum lead to rumors that the museum is being haunted by the ghost of a Pterosaur, ten-year-old Wilson Kipper and his friends set out to solve the mystery.
008-011.
Keywords: Natural history museums -- Juvenile fiction; Pterosauria -- Juvenile fiction; Detective and mystery stories; Best friends -- Juvenile fiction; Mystery and detective stories; Natural history museums -- Fiction; Museums -- Fiction; Pterosaurs -- Fiction; Dinosaurs -- Fiction; Best friends -- Fiction; Friendship -- Fiction; African Americans -- Fiction; Mystery fiction; Detective and mystery stories